Understanding the drivers of the live bird trade in Brazil - Maria Melo Azeredo, Luane; Nóbrega Alves, Romulo Romeu (Ethnobiology and Conservation, 2024)
In this work we sought to evaluate the factors that influence the public's interest in wild birds sold as pets in Brazil, and the relationship of those factors with new occurrences of birds outside their natural range. We compiled the richness of bird species traded in Brazil and obtained comparative data of public interest directed to these species through the Google Trend tool. In addition, we gathered data on biological attributes and the sale price of the species in the trade, to analyze which factors would be related to public interest. Then, factors related to public interest were used to assess whether there was a relationship with these new occurrences. The main founds indicated that the public interest is greater for songbirds, omnivores, which live in more open environments and are sold at lower prices. All those factors also showed to be related to the birds that presented new occurrences. The public's preference for birds more generalist and from more open environments are important results, as such factors generally indicate greater environmental tolerance, which may favor the establishment of these birds in new environments. Therefore, it is likely that species releases or escape from captivity, combined with their life history attributes, may favor the establishment of isolates in new environments. Thus, the present results demonstrate that actions aimed at the conservation of commercialized species are essential to reduce the interregional trade of species, and consequently reduce the impact on natural populations and reduce the potential for new biological introductions.